Genomic and morphological features of an Amazonian Bacillus thuringiensis with mosquito larvicidal activity - Veranilce Alves Muniz; Ricardo de Melo Katak; Lílian Caesar; Juan Campos de Oliveira; Elerson Matos Rocha; Marta Rodrigues de Oliveira; Gilvan Ferreira da Silva; Rosemary Aparecida Roque; Osvaldo Marinotti; Olle Terenius; Edmar Vaz de Andrade (AMB Express)
Abstract The occurrence of mosquito-borne diseases is increasing, and their geographical range is expanding due to climate change. New control measures are urgently needed to combat these debilitating and, in some cases, fatal diseases. Bacteria of the genus Bacillus are of interest due to the production of bioactive compounds, including those useful for insect control. The discovery and characterization of new species of Bacillus with mosquito larvicidal activity may offer opportunities to develop new products for vector control. In this study, we evaluated larvicidal activity, described morphological characteristics, and sequenced and analyzed the genome of a bacterial strain (GD02.13) isolated from the Amazon region. The metabolites produced by GD02.13 are as effective in killing Aedes aegypti larvae as the commercial product Natular™ DT (Spinosad). Furthermore, the morphological characteristics of the GD02.13 spores and crystal inclusions resemble those previously described for B. thuringiensis. A phylogenetic analysis based on 443 single-copy orthologs indicated that the bacterial strain GD02.13 belongs to the Bacillus thuringiensis species. Its genome, which was assembled and has a size of 6.6 Mb, contains 16 secondary metabolite biosynthetic gene clusters and genes encoding insecticidal proteins, predicted based on sequence similarity. The data obtained in this study support the development of new insecticide products based on the strain GD02.13 of B. thuringiensis.